Activated banana peel macrocomposite adsorbent for river water treatment: isotherm and kinetic studies. Issue 4 (10th April 2023) - Apandi, Najeeha Mohd; Muhamad, Mimi Suliza; Wee Yek, Tan; Sunar, Norshuhaila Mohamed; Nagarajah, Ramathasan
Abstract: This study investigates the potential of a hybrid process combining sand filtration column with activated banana peels macrocomposite (ABPM) adsorbent for river water treatment. Scanning electron microscopy (SEM) analysis displayed an irregular structure and high cavities of the banana peel adsorbent surface that caters to the deposition of contaminants, while energy-dispersive X-ray analysis detected major elements of the adsorbent, such as calcium, oxygen, silicon, and carbon. Fourier-transform infrared analysis of the banana peels adsorbent showed the presence of hydroxyl, acyl, amine, and alkene groups that were responsible for the adsorption process. The sand filtration column experiment was investigated to find out the removal of turbidity, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), and ammonia nitrogen (AN) where it resulted in the highest removal efficiency operated at a flowrate of 1.15 ml/s with >90% turbidity, 44% COD, 87% BOD, 75% TSS, and 54% AN removal. The adsorption isotherm was best described by the Langmuir model (R 2 > 0.98) compared to the Freundlich model (R 2 > 0.95). The pseudo-first-order kinetic model was the best fit for all the experimental data. The combination of sand filtration column with ABPM adsorbent is an efficient treatment solution for improving river water quality. HIGHLIGHTS: Studies on activated banana peels as an adsorbent is a remarkable function for water treatment. Significantly reduces the fruit waste disposal in landfills and practices the waste-to-wealth concept. Isotherm and kinetic studies also provide the best overall model for experimental data. Banana peel has a valuable potential as a natural adsorbent. Economical and reduces a negative impact on the environment. Graphical Abstract